2017
DOI: 10.1128/cvi.00456-16
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Based Immunotherapy To Treat and Prevent Infection with Hypervirulent Klebsiella pneumoniae

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp) strains are predicted to become a major threat in Asia if antibiotic resistance continues to spread. Anticapsular antibodies (Abs) were developed because disseminated infections caused by hvKp are associated with significant morbidity and mortality, even with antibiotic-sensitive strains. K1-serotype polysaccharide capsules (K1-CPS) are expressed by the majority of hvKp strains. In this study, K1-CPS-specific IgG Abs were generated by conjugation of K1-CPS to immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 49 publications
0
91
0
Order By: Relevance
“…Thus, the effective ability of anti-CPS antibody to promote killing of ST258 might be increased in the susceptible host (e.g., an individual with comorbidities or immunosuppression). An immunotherapy approach for K. pneumoniae could be extended to target lineages other than ST258, and such work is ongoing (43,44). Moreover, recent studies indicated that antibodies specific for K. pneumoniae lipopolysaccharide work synergistically with antibiotics to improve outcomes in mouse infection models (20).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effective ability of anti-CPS antibody to promote killing of ST258 might be increased in the susceptible host (e.g., an individual with comorbidities or immunosuppression). An immunotherapy approach for K. pneumoniae could be extended to target lineages other than ST258, and such work is ongoing (43,44). Moreover, recent studies indicated that antibodies specific for K. pneumoniae lipopolysaccharide work synergistically with antibiotics to improve outcomes in mouse infection models (20).…”
Section: Resultsmentioning
confidence: 99%
“…Kupffer cells lining the liver sinusoids are professional resident phagocytes that first encounter gut-derived bacteria and have been described as a highly effective filtering system between the digestive system and the rest of the body (11). It has been reported that depletion of Kupffer cells significantly increased the susceptibility of host mice to Listeria monocytogenes infection, resulting in 100% mortality of mice within 3 days of infection (12).…”
mentioning
confidence: 99%
“…The relevance of sex as a biological variable and rigor of experimental approaches were emphasized. Important reports on these and other trending topics were published in CVI (8)(9)(10)(11)(12)(13)(14). In this rapidly expanding scientific environment, CVI remained committed to disseminating discoveries and scientific knowledge with high scholarly and editorial standards, in line with those of other ASM journals and following the tradition and excellence of the society itself.…”
Section: A Springtime For CVImentioning
confidence: 89%